System Design: Data Flow Diagrams of Sales Process, a Case Study of CV. Jatayu Catra Internusa - Lila Setiyani; Evelyn Tjandra (Politeknik Piksi Ganesha Indonesia, 2022)
This study aims to analyze the flow of sales transaction data. The data flow is modeled using a data flow diagram. The procedure carried out for data flow analysis began by interviews with staff who handle sales, then proceeded to identify entities and documents that go in and out of these entities, then modelled the data flow into data flow diagrams, and taking into account the rules on data flow diagram modeling. The results of this study are data flow diagram modeling of sales transaction that can be used to perform advanced system models such as case modeling, entity relationship diagrams, and others.